MAIN DIRECTIONS OF EXPORTBOP PRODUCT DEVELOPMENT IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article examines the main directions of export production in the digital economy. At the same time, the article examines the problems associated with the use of international and national marketing. International marketing is analyzed as a means of shaping national production based on external market conditions, determining its specialization, and organizing, managing and controlling foreign economic and trade activities of companies. Methods for assessing the competitiveness of export products are analyzed. The impact of diversification, modernization and innovation factors affecting competitiveness is also analyzed, and their importance in increasing the country’s export potential is revealed and explained.